Report of the Working Group on ADP Matters ... - ICES (ICES Expert Group reports (until 2018), 2023)
At the 77th Statutory Meeting it was decided (C.Res.1989/2:8) that the working Group on ADP Matters (Chairman: Dr G. Stefansson, Iceland will meet at ICES Headquarters from 15-16 March 1990 to:a) consider and comment on a report being prepared by the Secretariat staff describing its present and anticipated computer needs and containing a recommendation for a replacement computer system for ICES Headquarters;b) consider and comment on a report to be prepared by a consultant who will be engaged to: i) evaluate the computer needs and proposed replacement system identified by the Secretariat and, based on this,ii) recommend the specific details and optimal configuration of such a system;c) ensure that compatibility and communication with computer systems in Member Country institutes and data centres is maintained in the recommended replacement system;d) advise the Bureau of the outcome of its review of the above items and recommend an appropriate course of action. ...